Peningkatan Ketuntasan Belajar siswa Konsep Lingkungan Menggunakan Multi Model Pada Siswa Kelas X.1 SMA Negeri 4 Bireuen - Jumiati Jumiati (Universitas Syiah Kuala, 2011)
The Use of Multiple Models in Environmental concepts in SMA Negeri 4 Bireuen. Research purpose is to know the process of learning outcomes through the use of Multi-model on the concept of Environment. The approach used was qualitative descriptive approach types of Class Actions. This study used two cycles with four components, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). Subjects in this study were students in grade lesson X.1 2008/2009 amounted to 36 people. The instrument used was the test at the end of each cycle. To find out the improvement process and the thoroughness of learning, percentage formula is used. The results showed that 44, 44% who have attained completeness in cycle 1. Cycle II obtained by the thoroughness of 88.89%. Students generally respond positively to learning. It is suggested that the use of multiple models can be used on other concepts in the biology of learning to encourage students in learning.